GIS Based Real Time Traveler Information System: An Efficient Approach to Minimize Travel Time Using Available Media - Hasnat, Md. Abul; Haque, Mohammad Mahmudul; Khan, Mumit (BRAC University, 2010)
Includes bibliographical references (page 5).